Empowerment Based on Non Formal Education Through Local Potential in The Processing of Lampung Coffee - Lintang Markhamah Watianur Azizah (Procedia of Social Sciences and Humanities, 2021)
Covid 19 has caused all sectors to weaken. Regional strength can be built through the economic recovery of each region, which is supported by educational empowerment programs to utilize the regional potential. The purpose of this study was to provide the results of developing entrepreneurial skills in students of the PAKET C equivalency program based on local potential through training in Lampung coffee processing. The skills provided include the production and marketing of Lampung coffee into processed food such as biscuits, air fresheners, and ready-to-brew ground coffee. Lampung coffee product marketing has been marketed throughout Indonesia and even abroad. This research uses a qualitative descriptive approach which is defined as a problem-solving procedure by describing the situation of the subject or object (person, institution, or society) based on real conditions. Collecting data using the method of observation, interviews, correspondence documentation, and literature study of relevant research to obtain secondary data. Data analysis using descriptive qualitative. The results showed that the students had the skills to produce and market Lampung coffee at PKBM Kencana. Every month each student earns 2 to 3 million. This research makes a scientific contribution to the study of non-formal education that leads to the quality of education in society.